Peran Kelompok Tani Dalam Meningkatkan Kesejahteraan Masyarakarat Di Desa Karangpranti Pajarakan Probolinggo - Ainol; Bukhori, Imam (KHIDMAH : Jurnal Pengabdian Masyarakat, 2021)
Abstrak Based on data from the Central Statistics Agency (BPS) the number of poor people in Indonesia in March 2019 reached 25,14 million people, or about 9,82% of the total population. The amount is reduced 530 thousand inhabitants compared to the position in September last year and shrink 805 thousand inhabitants compared to the position in March last year. (Viva Budy Kusnandar, 2019). It needs a special attention for the farmers, because the future of the farmers is essential for the continuity of production of farmers as the main meal of the nation of Indonesia. In improving a production of farmers, so the main factor and increased development and welfare for farmers. Farmer groups also require strengthening in order that the farmers can prosper. The number of farmer groups formed can result in many groups of farmers who have been inactive. Each member of the group of farmers can use this institution in the increase of performance for the welfare of the farmers. The role and function of farmer groups have a very important role in mobilizing development in the field of agriculture. The strengthening of institutions that need to be implemented so that it can memotivitasi as well as guidance to the farmers are able to cooperate in the field of economy. The efforts made in the strengthening of the business groups of farmers, namely with the guidance and support to farmers in order to be able to cooperate with well in the economic field. So farmer groups can develop well need to be given venture capital, as well as coaching and training to farmer groups, in order to increase the capacity of human resources, namely by carrying out training and mentoring to all the committee and members. In the process of improving groups of farmers conducted by the instructor in terms of empowerment. Although in terms of coaching and mentoring farmer groups can also invite NGOS and other organizations that are considered to be the professional that will be included on the strengthening and empowerment of farmer groups. Key word : The Role Of Farmer Group, Well-Being, Community